AKUNTANSI PENGEMBANG REAL ESTATE MENURUT PERNYATAAN STANDAR AKUNTANSI KEUANGAN (PSAK) NO 44 PADA PT HARVEST PROPERTI SAMARINDA - -, Edi Suwikno (EKONOMIA, 2014)
Real estate development activities under SFAS 44 are land acquisition activities for then built residential or commercial buildings or industrial buildings. The buildings are intended to be sold or rented out, as a whole or in retail. Real estate development activities also include the acquisition of land plot, then sold the land without buildings. matters not provided for in this statement should be treated with reference to generally accepted accounting principles. The scope of this Statement shall be applied to the company's real estate development activity, although the activity of real estate development is not the primary activity of real estate.The problem posed in this study are Is the financial statements present management policies on PT Harvest Property has been in accordance with Statement of Financial Accounting Standards (SFAS) No. 44.The hypothesis of this study is the management policy of presenting the financial statements in PT Harvest Property has not been in accordance with Statement of Financial Accounting Standards (SFAS) No. 44Basic theory used is Pernytaan Theory of Accounting and Financial Accounting Standards (SFAS)This study uses a comparative analysis tool that compares the company's financial statements with the financial statements in accordance with Statement of Financial Accounting Standards (SFAS) No. 44 of the Real Estate Development Activities Based on the results of research and discussion, the conclusions of this study as follows :Financial Position are made by companies in the real estate inventory asset accounts are not separated, which should be separated between the supply of land ready for sale, undeveloped land and land under developmentReports Corporate Performance made by the company are also not separate the costs, the cost of land acquisition and pre- acquisition costs of land. On account of the cost of the project according to the company should be separated into costs that are directly related to the project and the costs attributable to the development of real estate.Based on the description above, the hypothesis in this study that the alleged financial statements present management policies on PT. Harvest Property has not been in accordance with Statement of Financial Accounting Standards (SFAS) No. 44 is received.